2020
DOI: 10.3389/fnagi.2020.580068
|View full text |Cite
|
Sign up to set email alerts
|

P2X4R Overexpression Upregulates Interleukin-6 and Exacerbates 6-OHDA-Induced Dopaminergic Degeneration in a Rat Model of PD

Abstract: The pathogenesis of Parkinson’s disease (PD) remains elusive. Current thinking suggests that the activation of microglia and the subsequent release of inflammatory factors, including interleukin-6 (IL-6), are involved in the pathogenesis of PD. P2X4 receptor (P2X4R) is a member of the P2X superfamily of ion channels activated by ATP. To study the possible effect of the ATP-P2X4R signal axis on IL-6 in PD, lentivirus carrying the P2X4R-overexpression gene or empty vector was injected into the substantia nigra (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 111 publications
(159 reference statements)
0
9
0
Order By: Relevance
“…Although the pro-in ammatory role of IL-6 is well-de ned after acute stroke injury, reduced IL-6 levels may indicate cerebroprotective effects of P2X4R KO during early stroke injury timepoints. Although the exact mechanism of how P2X4R activates IL-6 is not clear, we and others have shown that pro-in ammatory effects of P2X4R activation might indirectly contribute in stroke injury [23].…”
Section: Discussionmentioning
confidence: 87%
“…Although the pro-in ammatory role of IL-6 is well-de ned after acute stroke injury, reduced IL-6 levels may indicate cerebroprotective effects of P2X4R KO during early stroke injury timepoints. Although the exact mechanism of how P2X4R activates IL-6 is not clear, we and others have shown that pro-in ammatory effects of P2X4R activation might indirectly contribute in stroke injury [23].…”
Section: Discussionmentioning
confidence: 87%
“…Purinergic receptors have a complex role both in promoting and preventing inflammation. For instance, the potentiation of P2X4R signaling favors a switch to an anti-inflammatory phenotype in microglia [ 58 ], but P2X4R overexpression is also related to an upregulation of cytokines such as IL-6 and inflammation [ 14 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that these receptors can influence each other’s expression (reviewed in [ 11 ]). The role of P2X4R in neurodegeneration is less clear, although it is considered a central player in the pathogenesis of chronic and neuropathic pain and allodynia [ 14 , 15 ]. It is also involved in multiple pathologies including asthma, rheumatoid arthritis, Duchenne muscular dystrophy, brain tumors, and neurodegenerative diseases, including PD and amyotrophic lateral sclerosis [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…P2X7 receptor inhibition has neuroprotective and neuroregenerative effects in various models of PD through anti-inflammatory actions along with modulation of the microglial activation state and cytokine release [ 202 205 ]. Also, overexpression of P2X4 receptors upregulates IL-6 and exacerbates 6-OHDA-induced dopaminergic degeneration in the rat model of PD [ 206 ]. A very recent paper suggests that P2X4 receptor activation might inhibit neuronal autophagy through regulation of the BDNF/TrkB signaling pathway, leading to dopaminergic neuron damage in the substantia nigra and the further inhibition of P2X4-mediated autophagy [ 207 ].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…Overexpression or activation of P2X4Rs is associated with increased dopaminergic degeneration [ 206 , 207 ]…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%